LITERATURE AND TEACHING: CANDIDO, A CRITIC IN THE CLASSROOM - Rolim de Lima, Neivana; de Souza Esmeraldo, Moema (Revista Gênero e Interdisciplinaridade, 2026)
This article discusses Antonio Candido’s perception of critical construction, historiography, and consequently, studies of Literary Theory and Comparative Literature in Brazil. The research is characterized as theoretical-bibliographical in nature, based on propositions by Antonio Candido (2019), Sandra Nitrini (2019), Esmeraldo (2022, 2024), and Waltencir Alves de Oliveira (2019). The aim is to present Candido’s framework and the first steps he took to establish himself as a revolutionary figure in the field of Comparative Literature in Brazil. To this end, the texts chosen as objects of investigation are *In the Classroom* (Candido, 2008), *How and Why I Am a Critic* (Candido, 2019), and *The Right to Literature* (Candido, 2019), as well as *How and Why I Am a Novelist* (Alencar, 1893), which are analyzed from the scope delimited for this article, in dialogue with the texts of previously mentioned theoretical perspective. The analysis highlights the relevance of Antonio Candido’s critical thought for the constitution of literary studies in Brazil, emphasizing his contribution to the articulation between criticism, historiography, and comparative literature.